2019
DOI: 10.1037/neu0000504
|View full text |Cite
|
Sign up to set email alerts
|

HIV and age underlie specific patterns of brain abnormalities and cognitive changes in high functioning patients.

Abstract: Objective: Findings on the influence of age and HIV on brain and cognition remain equivocal, particularly in aviremic subjects without other age or HIV-related comorbidities. We aimed to (a) examine the effect of HIV status and age on structural brain measurements and cognition, and (b) apply the machine learning technique to identify brain morphometric and cognitive features that are most discriminative between aviremic subjects with HIV on stable combination antiretroviral therapy (cART) and healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Age was the only primary predictor in all studies, but in eight studies, age was investigated as a co-primary exposure along with a HIV-related variable such as duration of HIV infection [37] or a non-HIV related factor such as education [46] and alcohol use [47]. Neurocognition was also the sole primary outcome of interest in all but five studies [29,30,35,36,48], which also identified the effect of age on changes in neuroimaging.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Age was the only primary predictor in all studies, but in eight studies, age was investigated as a co-primary exposure along with a HIV-related variable such as duration of HIV infection [37] or a non-HIV related factor such as education [46] and alcohol use [47]. Neurocognition was also the sole primary outcome of interest in all but five studies [29,30,35,36,48], which also identified the effect of age on changes in neuroimaging.…”
Section: Methodsmentioning
confidence: 99%
“…The highest prevalence rate of HAND was found in a study where a large proportion (81%) of HIV + participants had substance use disorders [64]. Four out of eight studies [36,37,39,53] classified HAND clinical sub-categories, with ANI being the most prevalent (range: 53%-74%) in three studies, while MND was the predominant classification in one study (55%) [39]. Four of the studies compared HAND prevalence between age groups [37,58,62,64].…”
Section: Hand Prevalencementioning
confidence: 98%
See 3 more Smart Citations